It's Enough to Make You Sick: The Failure of American Health Care and a Prescription for the Cure - Lobosky, Jeffrey M. (Rowman & Littlefield Publishers, 2012)
It's Enough to Make You Sick explains how the American health care system developed and how it has deteriorated into a national disgrace. Lobosky indicts the special interests who have played a role in the demise of American health care, examines the current attempts at reform, and offers a practical, compassionate blueprint for effective change.